Leveraging a CHO cell line toolkit to accelerate biotherapeutics into the clinic. (7th September 2017) - Wright, Chapman; Alves, Christina; Kshirsagar, Rashmi; Pieracci, John; Estes, Scott
Abstract : The Biogen upstream platform is capable of delivering equivalent quality material throughout the cell line generation process. This allows us to rapidly deliver high‐quality biopharmaceuticals to patients with unmet medical needs. The drive to reduce time‐to‐market led the cell engineering group to develop an expression system that can enable this strategy. We have developed a clonal Chinese Hamster Ovary (CHO) host cell line that can routinely produce consistent antibody material at high titers throughout the cell line generation process. This host line enables faster delivery of early phase material through use of the highly productive stable pool or a mixture of high performance clones. Due to unique characteristics of this cell line, the product quality of material from early cell populations is very comparable to material from the final clones. This lends itself to a "fast‐to‐tox" strategy whereby toxicology studies can be performed with representative material from an earlier cell population, thus accelerating the clinical timelines. Our new clonal host offers robust and consistent performance that enables a highly productive, flexible process and faster preclinical timelines. © 2017 American Institute of Chemical Engineers Biotechnol. Prog ., 33:1468–1475, 2017